Knowledge, Attitude, Practice of Iranian Physicians about COVID-19 in Iran - ghasemisarukolai, maryam (Advances in Social Sciences Research Journal, 2021)
As a result of the global crisis caused by the coronavirus outbreak in late December 2019, Iran was also severely affected. The three provinces of Tehran, Mazandaran, and Gillan were high-risk cities exposed to infection and grievously damaged. Therefore, we decided to look at the level of knowledge, depth of attitude, and quality of physicians' practice in these three provinces. The most significant goal was to assess the level of KAP relative to the COVID-19 virus to provide comprehensive information to identify the strengths and weaknesses of the treatment staff to better cope and more effectively prevent and control critical situations. For research methodology, a cross-sectional study was performed on a sample of 300 people using a self-made questionnaire. An online questionnaire via virtual networks and a paper questionnaire were also distributed by the principal author in medical hospitals, which included four sections: demographic information, knowledge, attitude, and practice. Cronbach's alpha confirmed the validity and reliability of each component. The final results prove that the knowledge of physicians was acceptable and significant at the level of 0.05. Physicians' attitudes showed a level of fear and anxiety that was significant according to a one-sample t-test and chi-square (Sig <0.05). In order to rank the physicians' practice, a T-test was used, and the results of the Friedman test in the first stage of the Chi-square test showed that the significance level is 0.05. Looking at the research results, it can be said that the development of educational programs can have a beneficial effect in increasing physicians' knowledge and controlling the disease as effectively as possible. Also, due to the attitude associated with stress and fear, it can be seen that providing laboratory and treatment equipment has been one of the concerns of physicians.